Penerapan model pembelajaran time token untuk meningkatkan keterampilan komunikasi pada pembelajaran IPS kelas V sekolah dasar - Nur Farikah Rahmawati; Siti Istiyati; Yulianti Yulianti (Didaktika Dwija Indria, 2020)
This research was a class action research in order to improve communication skills in social studies learning through Time Token learning models for 5th grade of elemtary school students at Surakarta 2019/2020 Academic Year. The study was conducted in two cycles consisting of four meetings with stages, including planning, action, observation, and reflection. Research data collection was done by interviewing, observing communication skills, and document studies technique. The validity of the data used is content validity, source triangulation and technique triangulation. Data analysis techniques with Mile and Huberman’s interactive analysis models which include data collection, data reduction, data presentation, and drawing conclusions. The result of the study increased from pre-action activities y 50.91 (5,88%), an increase of 71.11 (41.17%) the first cycle , and 76.73 (82.35%) the second cycle. Based on the results of this reaultsof this research, concluded that communication skills in social studies learning in 5th grade students had increased by implementing the Time Token learning model.